KONTEMPLASI: TATA SUSILA PEMBUATAN SARANA UPACARA (BANTEN) PADA KEHIDUPAN MASYARAKAT BALI - Ida Ayu Devi Arini (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The purpose of this study is to conduct a study of the phenomenon in the life of the Hinducommunity, namely the shift in the ethics of the Balinese Hindu community, especially the bantenin the process of making the offering itself. The current phenomenon, there is a shift and this tendsto cause conflict with the sacred texts of Hinduism. This phenomenon must be immediately founda solution so that there are no continuous and hereditary errors. This research is a qualitativeresearch. The data sources consist of primary data, namely the results of observations andinterviews with experts. While secondary data in the form of books, scientific journals that supportthe analysis. The collected data is then selected to help analyze, analyze and the last step isdrawing conclusions. The results of this study are expected to be able to provide awareness to thepublic, especially lati offerings, so that they can re-learn the knowledge contained in Hindu sacredtexts related to the ethics of making offerings and procedures for preparing and managingofferings.